A origem intelectual das orações em tupi de André Thevet e Yves d’Evreux (séculos XVI-XVII): algumas hipóteses (Revista de Estudos da Linguagem, 2002)
The aim of this study is to identify the intellectual origins of theprayers in Tupi, published by the French clerics André Thevel andYves d’Evreux in the XVI and XVII centuries.